HUBUNGAN PENGETAHUAN DAN DUKUNGAN KELUARGA DENGAN KEPATUHAN PASIEN DALAM PERAWATAN LUKA GANGGREN - Noer, Sitti Fauziah; Ginting, Daniel Suranta; Kadir, Abd; Triswanti, Triswanti; Herawati, Nurul (Ensiklopedia of Journal, 2024)
Based on data obtained at RSUD Bangkinang in 2021, the amount of data and patients with diabetes mellitus amounted to 5117 people and patients with gangrene wounds undergoing treatment in 2022 were 48 patients. The type of research in this study is analytic with a cross sectional design. The population in this study were all patients with diabetes mellitus gangrenous wounds in the Surgical Clinic of Bangkinang Hospital in 2022, namely 48 people with a sample of 48 people using the total sampling technique. Data collection tools using questionnaires. Data analysis used in this study was univariate and bivariate analysis. The results showed that there was a relationship between knowledge and patient compliance in the treatment of gangrene wounds at Bangkinang Hospital with a p value of 0.001 and there was a relationship between family support and patient compliance in the treatment of gangrene wounds at Bangkinang Hospital with a p value of 0.00. It is recommended that the patient's family can increase emotional support, appreciation / assessment support, instrumental support and information support.Keywords: Knowledge, family support, adherence to gangrene wound care